Topical Growth Factors for the Treatment of Facial Photoaging: A Clinical Experience of Eight Cases - Pamela, Ruri D (The Journal of clinical and aesthetic dermatology, 2018)
Chronic exposure to solar ultraviolet irradiation can result in facial fine lines and wrinkles, poor texture, and sagging skin. Growth factors are polypeptides or proteins that play a key role in the regulation of a number of physiological processes. Topical application of growth factors also reduces signs of photoaging, promotes fibroblast and keratinocyte proliferation, and induces extracellular matrix formation. This study evaluated the efficacy of topical growth factor after microneedling treatment for the reduction of visual signs of facial photoaging in Fitzpatrick skin types III to IV. Eight patients applied 2mL of gel containing a mixture of four different growth factors to photodamaged facial skin after microneedling procedures. The gel contained a biosynthetic mixture of epidermal growth factor, fibroblast growth factor, hepatocyte growth factor, and insulin-like growth factor. This was performed every 10 days, with three treatments total. An independent physician evaluator used the Fitzpatrick wrinkle scale to evaluate clinical photographs that were taken pre- and posttreatment (at before treatment and after four weeks of treatment). Assessment of side effects was performed after the second and third treatments. Patient questionnaires were completed in the fourth week. Based on the independent physician's clinical assessment, seven of the eight patients showed an improvement in texture, fine lines, and wrinkles, especially in the periorbital region. According to the patient questionnaire, four of the eight patients felt their wrinkles were improved, while all patients felt their skin texture was smoother. Five of the eight patients experienced slight redness at 1 to 2 days after treatment. The application of topical growth factors after microneedling can be useful to reduce visual signs of facial photoaging by improving skin texture and minimizing the appearance of fine lines and wrinkles.